Binding of Candida albicans to Immobilized Amino Acids and Bovine Serum Albumin - Hawser, Stephen P. (American Society for Microbiology, 1998)
In this study, we examined the binding of Candida albicans synchronized yeast-phase cells to plastic, immobilized amino acids and bovine serum albumin (BSA) and quantified the binding by using an XTT tetrazolium salt assay and absorbance determination. Our results show that C. albicans binds efficiently and specifically to several nonpolar aliphatic amino acids and positively charged amino acids and to BSA immobilized on tissue culture plastic but not to polar uncharged, negatively charged, or aromatic amino acids. Adhesion of yeasts to immobilized amino acids was not affected by preincubation of cells with BSA, whereas binding to immobilized BSA was affected by preincubation of yeasts with alanine, proline, and leucine but not by arginine or lysine. The ability to distinguish the chirality of these amino acids was also examined by using both the d and l amino acid configurations, and the results show that C. albicans yeasts recognize only the l configuration of these amino acids. The observations that C. albicans specifically binds to certain amino acids indicate that these amino acids may prove useful tools for studying the binding interactions of C. albicans yeasts with host proteins such as components of the extracellular matrix.